(untitled) (Research, Society and Development, 2023)
Objective: To verify the main challenges in learning the subject of Physics in secondary education in public schools and to contribute with information about effective didactic strategies to improve this scenario. Method: This is a qualitative and exploratory literature review, with a theoretical approach, using the platforms: Scientific Electronic Library Online (SCIELO), digital repository LUME, IEE Xplore, ERIC, Microsoft academic, Science research, electronic journals and the CAPES journal, between the periods of 2018 to 2023. Results: After applying the defined inclusion and exclusion criteria, 13 articles were added. It was identified that high school students from public schools face many difficulties related to learning Physics due to several factors, such as little understanding of mathematical knowledge, lack of pedagogical strategies, inadequate school infrastructure, lack of qualified professionals. Conclusion: it is concluded that this work allowed us to point out the needs that need our attention and we understand that the quality of physics teaching requires more investment in public schools for a better teaching structure and its quality for students.